PENGARUH TINGKAT LITERASI KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN PADA UMKM DI INDONESIA - Labbaika Dwi Ayu Rahmawati (ITB AAS Indonesia, 2025)
This study aims to analyze the effect of financial literacy levels on the quality of financial reports in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs play an important role in the Indonesian economy, contributing around 60% of Gross Domestic Product (GDP) and absorbing more than 97% of the workforce. However, many MSMEs face challenges in good financial management, which is often caused by low levels of financial literacy. This study uses a qualitative descriptive approach with a sample of 300 MSMEs from several major cities in Indonesia. The results of the study indicate that there is a significant positive relationship between the level of financial literacy and the quality of financial reports, with a correlation coefficient of 0.65. Increasing financial literacy is expected to improve the quality of financial reports, which in turn supports the growth and sustainability of MSMEs. It is recommended that the government and related institutions develop training and education programs to improve financial literacy among MSMEs.